A CRITICAL ANALYSIS OF MEDO DHATU : AN APPROACH TO EXPLORE THE PHYSIOLOGICAL ENTITY - Mandal Nisith Kumar; Kundu Suman; JanaDipanjan; Maity Gouranga; Tripathi Joydip (International Journal of Applied Ayurved Research, 2019)
Ayurveda is a well documented science on human health. All the basic segments of medical sciences including anatomy, physiology, pathology, pharmacology are well described in Ayurvedic literatures as per Ayurvedic parlance. According to Ayurveda, Dhatu are considered as one of the basic functional as well as structural component of human body. There are seven basic Dhatu are present in human physiology as per Ayurvedic parlance.Medo Dhatu is a Dhatu which bear a resemblance with adipose tissue in both structural and functional aspect. This review aims at scanning of scientific articles to provide a comprehensive knowledge about the conventional entity of Medo-dhatu.